Análisis de eficiencia del sector industrial manufacturero en cinco países suramericanos, 1995-2008. (2015)
This article measures the technical efficiency of five south american countries in manufacturing during 1995-2008. Through an analysis of stochastic frontier efficiency is estimated to test whether agglomeration contributes to get efficient productivity closer to its border. Translog production function is used, because it allows technological changes and variations in the proportions of inputs and outputs of the elasticity of scale. The results show that in the manufacturing sector improvements in technical efficiency and technological changes were not generated during these fourteen years. Evidence suggests that environmental variables determined by the gross formation of total fixed capital or only in machinery and equipment influence the behavior of the sector.